Saving the security state : exceptional citizens in twenty-first-century America - Grewal, Inderpal (Next wave (Duke University Press), 2017)
Inderpal Grewal traces the changing relations between the US state and its citizens in an era she calls advanced neoliberalism, under which everyday life is militarized, humanitarianism serves imperial aims, and white Christian men become exceptional citizens tasked with protecting the nation from racialized others.